The effects of component rotation on H/V spectra: a comparison of rotational and translational data - Nawrocki, Dariusz; Mendecki, Maciej; Teper, Leslaw (Geology, Geophysics and Environment, 2024)
The presented investigation focused on site effect estimations, specifically resonance frequency and amplification. These estimations were carried out for both rotational and translational signals, using waveforms from mining-induced seismic events. Site effect parameters were calculated using the horizontal-to-vertical spectral ratio (HVSR) technique, which is commonly applied to translational records by comparing the spectral ratio between horizontal and vertical components. In this study, we also applied the horizontal-to-vertical (H/V) ratio to rotational records. However, due to the different orientations of motion propagation, we introduced the spectral H/V ratio for rotational motion as the torsion-to-rocking spectral ratio (TRSR). Furthermore, we analyzedthese signals according to two approaches. First, we estimated the site effect parameters for directly registered signals, and secondly, we considered rotated components by varying the angle from 0° to 180° in 5-degree increments. Generally, the H/V curves indicated two peaks for translational motions and four peaks for rotational motions. The averaged H/V spectra and spectra obtained for different angles of component rotation showed insignificant fluctuation in amplification values for both rotational and translational motions. However, when comparing each component’s spectrum for all angles, we observed changes in the site effect parameter values for both motion types. Radar plots depicting amplification values versus rotation angles for separated components revealed characteristic fluctuations, suggesting local anisotropy. Moreover, when comparing the radar plots between rotational and translational results, it was evident that rotational resonance frequencies shifted to higher frequency values, potentially indicating shallower geological layers as their source.